Extraordinary Manifestation of Evanescent Wave in Biomedical Application - Angelsky, Oleg V.; Zenkova, Claudia Yu; Hanson, Steen G.; Zheng, Jun (Frontiers in Physics, 2020)
The paper summarizes the latest obtained results illustrating the rectilinear and rotational motion of micro-objects in a biological environment. Such a motion is stipulated by the action of the optical force, on the one hand, and the special influence of the toque of the evanescent wave, on the other one. The reason of this unusual action is the presence of a transverse spin component of the evanescent wave. This feature appears due to the method of excitation: a linearly polarized wave with the azimuth of polarization of 45° at total internal reflection (TIR) at the interface of a prism and a biological medium is used. The objects of the study were gold micro-particles located in a biological environment and red blood cells (RBC) in blood plasma. We demonstrate the possibility for controlling these objects using an evanescent wave under specially selected experimental conditions. The obtained results are highly relevant in modern pharmacology and biomedicine.